Sleep deprivation exhibits an age-dependent effect on infraslow global brain activity - Yibing Yang; Weiwei Zhao; Yutong Mao; Tianxin Mao; Yao Deng; Yifan Yang; Hengyi Rao; Xiao Liu (Proceedings of the National Academy of Sciences, 2026)
Infraslow (<0.1 Hz) global brain activity, quantified by the global mean blood-oxygenation-level-dependent (gBOLD) signal in resting-state functional magnetic resonance imaging (fMRI), is elevated during sleep and coupled to cerebrospinal fluid (CSF) dynamics, a key pathway for the brain waste clearance implicated in neurodegenerative disorders such as Alzheimer’s disease. However, the effect of sleep deprivation on gBOLD activity and its interaction with aging remain poorly understood. Using a rigorously controlled in-laboratory total sleep deprivation (TSD) protocol, we demonstrate that TSD significantly increases both the gBOLD signal amplitude and its coupling with CSF flow, suggesting a compensatory mechanism that may enhance glymphatic clearance following acute sleep loss. Notably, these TSD-induced enhancements exhibit robust age dependency, with markedly attenuated responses in midlife adults (40 to 50 y). The absence of this compensatory mechanism in midlife may exacerbate age-related impairments in neurotoxic clearance and increase dementia susceptibility, thereby offering mechanistic insights into the nexus between sleep disruption, aging, and neurodegeneration.